2016
DOI: 10.5751/es-08684-210320
|View full text |Cite
|
Sign up to set email alerts
|

Forests as landscapes of social inequality: tropical forest cover and land distribution among shifting cultivators

Abstract: ABSTRACT. Can social inequality be seen imprinted in a forest landscape? We studied the relationship between land holding, land use, and inequality in a peasant community in the Peruvian Amazon where farmers practice swidden-fallow cultivation. Longitudinal data on land holding, land use, and land cover were gathered through field-level surveys (n = 316) and household interviews (n = 51) in 1994/1995 and 2007. Forest cover change between 1965 and 2007 was documented through interpretation of air photos and sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Increased built-up area and reduced agricultural area, water bodies and forest area have also been reported elsewhere [28]. There is reported correlation between land holding, land use and forest cover distribution [29]. The results from this study however differ from that of Ouedraogo, et al [30] covering 1990, 2000 and 2013.…”
Section: Land Cover Transitions (1973-2013)supporting
confidence: 42%
“…Increased built-up area and reduced agricultural area, water bodies and forest area have also been reported elsewhere [28]. There is reported correlation between land holding, land use and forest cover distribution [29]. The results from this study however differ from that of Ouedraogo, et al [30] covering 1990, 2000 and 2013.…”
Section: Land Cover Transitions (1973-2013)supporting
confidence: 42%
“…resources), which leads to inequality and poor land management. Inequality is driven by different land-use practices and investment choices that fail to distribute resources equally (Coomes et al, 2016). Inadequate distribution forces more land to be converted, which can lead to a cycle of poor land management and social inequality and pushes development away from environmental sustainability (Hasegawa et al, 2019;Boyce, 1994;Cumming and von Cramon-Taubadel, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Experience in Asia has shown that providing broader livelihood options and alternative income generating activities outside forestry sector could help in poverty reduction activities for forest dependent activities [24]. This is in line with opinion that ecological conditions is an important pre-requisite used by resource users to develop their livelihood activities and also leverage on sustainable development [25]. (3) Another means of supporting the communities is to provide some fund for micro-finance on a revolving basis.…”
Section: Recommendationmentioning
confidence: 62%